The effects of cognitive behavioral therapy on self-esteem among couples with infertility - Ehteram Yousefi; Mitra Tadayon Najafabadi; Marzieh Talebzadeh Shooshtari; Mohammad Hussein Haghighizadeh (Shahrekord University of Medical Sciences, 2021)
Background and aims: Infertility is the inability to conceive after one-year sexual activity without contraception. It can be associated with different psychological consequences. The aim of this study was to evaluate the effects of cognitive behavioral therapy (CBT) on self-esteem among infertile couples. Methods: This randomized controlled trial was conducted in 2018 with a two-group pretest-posttest design. Participants were thirty infertile couples (60 individuals) who referred to the infertility clinic of Imam Khomeini hospital, Ahvaz, Iran. Couples with score 21 or less for the Eysenck Self-Esteem Questionnaire were randomly allocated to a 30-person control and a 30-person intervention group. Participants in the intervention group received CBT in eight sixty-minute weekly sessions, while their counterparts in the control group received no education. A demographic questionnaire and the Eysenck Self-Esteem Questionnaire were used for data collection. The data were analyzed through the SPSS software (v. 24.0) and the chi-square, independent-sample t, and paired-sample t tests. Results: There was no significant difference between the intervention and the control groups respecting the pretest mean score of self-esteem (12.93±3.31 vs. 12.8±2.58; P=0.863). The posttest mean score of self-esteem in the control group was 12.76±2.47 with no significant change compared with the pretest (P=0.907), while the mean score of self-esteem in the intervention group significantly increased to 21.43±3.54 at posttest (P<0.001). The posttest mean score of self-efficacy in the intervention group was significantly more than the control group (P<0.001). Conclusion: CBT can significantly improve self-esteem among couples with infertility